2022
DOI: 10.1007/s40820-022-00873-x
|View full text |Cite
|
Sign up to set email alerts
|

Natural Stibnite for Lithium-/Sodium-Ion Batteries: Carbon Dots Evoked High Initial Coulombic Efficiency

Abstract: Highlights The chemical process of local oxidation–partial reduction–deep coupling for stibnite reduction of carbon dots (CDs) is revealed by in-situ high-temperature X-ray diffraction. Sb2S3@xCDs anode delivers high initial coulombic efficiency in lithium ion batteries (85.2%) and sodium ion batteries (82.9%), respectively. C–S bond influen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 51 publications
4
31
0
Order By: Relevance
“…For the bare Zn electrode, the rough electrode surface usually generates uneven Zn 2+ flux at the electrode/electrolyte interface, triggers the accumulation of the Zn nucleus, and acts as a charge-rich center for the further amplified growth of Zn dendrites ( Zhou J et al, 2021 ). In addition, the enlarge exposed surface area would accelerate the HER rate and by-product formation, leading to a low CE and even battery failure ( Liu et al, 2022b ; Xiang et al, 2022 ). By contrast, with the metal–chelate interphase, Zn 2+ ions are easily anchored on the cross-linked network of TA molecule, restricting the uncontrollable lateral diffusion of Zn 2+ and thus producing homogenous nucleation sites for the even Zn deposition.…”
Section: Resultsmentioning
confidence: 99%
“…For the bare Zn electrode, the rough electrode surface usually generates uneven Zn 2+ flux at the electrode/electrolyte interface, triggers the accumulation of the Zn nucleus, and acts as a charge-rich center for the further amplified growth of Zn dendrites ( Zhou J et al, 2021 ). In addition, the enlarge exposed surface area would accelerate the HER rate and by-product formation, leading to a low CE and even battery failure ( Liu et al, 2022b ; Xiang et al, 2022 ). By contrast, with the metal–chelate interphase, Zn 2+ ions are easily anchored on the cross-linked network of TA molecule, restricting the uncontrollable lateral diffusion of Zn 2+ and thus producing homogenous nucleation sites for the even Zn deposition.…”
Section: Resultsmentioning
confidence: 99%
“…30 Thus, with the increase of CDs, CDs agglomerate together gradually to form large clusters. 31 Figure 2a displays the XRD patterns of the samples. Obviously, two peaks at 24.6 and 43.6°present in the samples are attributed to the (002) and (100) diffraction peaks of carbon, respectively, which are indicative of amorphous carbon.…”
Section: Resultsmentioning
confidence: 99%
“…In general, nanosized CDs are unstable in solution, which are prone to agglomerate owing to the high content of OFGs and surface energy . Thus, with the increase of CDs, CDs agglomerate together gradually to form large clusters …”
Section: Results and Discussionmentioning
confidence: 99%
“…Besides metal sulfide composition, low-cost carbonaceous materials have also been comprehensively used to embellish anode materials due to their good electric conductivity, which can improve energy storage properties. 27,[52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68] Although previous efforts have made considerable achievements in adjusting the electrochemical performance, it is still a serious challenge to harmonize the composition and microstructures at the same time in a designable and controllable manner. Herein, we designed pea-like MoS 2 @NiS 1.03carbon (MoS 2 @NiS 1.03 -C) heterostructure hollow nanofibers using a simple electrospinning and thermal treatment method.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, heterostructure Sb 2 S 3 /MoS 2 , 15 MnS‐MoS 2 , 25 Bi 2 S 3 /MoS 2 , 44 Ni 3 S 2 @MoS 2 , 50 and SnS‐MoS 2 51 have been reported that can deliver high electrochemical performance. Besides metal sulfide composition, low‐cost carbonaceous materials have also been comprehensively used to embellish anode materials due to their good electric conductivity, which can improve energy storage properties 27,52–68 . Although previous efforts have made considerable achievements in adjusting the electrochemical performance, it is still a serious challenge to harmonize the composition and microstructures at the same time in a designable and controllable manner.…”
Section: Introductionmentioning
confidence: 99%